Nepal’s Transit Route Negotiation with India and China - Giri, Naresh (Journal of Foreign Affairs, 2023)
The geographical disadvantage faced by landlocked countries hampers their overall development, prompting international law to grant certain rights to secure their access to coastal areas. Nepal, as a landlocked country, has encountered numerous challenges in negotiating transit routes with its immediate neighbors, China and India, in order to realize the rights guaranteed by international law to landlocked nations. The transit right serves as a lifeline for Nepal to access third countries, but recurrent blockades from its southern neighbor have created uncertainty regarding the southern route to seaports. While Nepal has signed the Transit Transport Agreement and its protocol with its northern neighbor, China, there has been limited progress in developing connectivity infrastructure. This paper argues that ensuring uninterrupted access through the southern route is vital for Nepal from an economic perspective. However, the development of an alternative route through the north is not only crucial for contingency situations but also for unlocking new opportunities.